2013
DOI: 10.5194/acp-13-5831-2013
|View full text |Cite
|
Sign up to set email alerts
|

Black carbon physical properties and mixing state in the European megacity Paris

Abstract: Aerosol hygroscopicity and refractory black carbon (rBC) properties were characterised during wintertime at a suburban site in Paris, one of the biggest European cities. Hygroscopic growth factor (GF) frequency distributions, characterised by distinct modes of more-hygroscopic background aerosol and non- or slightly hygroscopic aerosol of local (or regional) origin, revealed an increase of the relative contribution of the local sources compared to the background aerosol with decreasing particle size. BC-contai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
206
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(233 citation statements)
references
References 86 publications
(117 reference statements)
16
206
6
Order By: Relevance
“…These ratios are almost a factor of 1.5 lower than our ratio of 14.3 ± 4.4 ng m −3 ppb −1 , although the EC values from the single-particle soot photometer (SP2) and the Sunset (TOT) instruments are directly comparable (Kondo et al, 2011b); for example, Laborde et al (2013) reported a slope of 1.05 between the two methods. It is reasonable therefore to explain this difference with different air mass history (i.e.…”
Section: Polluted Air In the Transition Seasonsmentioning
confidence: 57%
“…These ratios are almost a factor of 1.5 lower than our ratio of 14.3 ± 4.4 ng m −3 ppb −1 , although the EC values from the single-particle soot photometer (SP2) and the Sunset (TOT) instruments are directly comparable (Kondo et al, 2011b); for example, Laborde et al (2013) reported a slope of 1.05 between the two methods. It is reasonable therefore to explain this difference with different air mass history (i.e.…”
Section: Polluted Air In the Transition Seasonsmentioning
confidence: 57%
“…Atmospheric lightabsorbing particles that arise from biomass burning play an important role as a driver of global warming (Favez et al, 2009;Hegg et al, 2010;Lack et al, 2012;Laborde et al, 2013;Srinivas and Sarin, 2013). According to the IPCC report (Boucher and David, 2013;IPCC, 2013), the climate forcing of black carbon aerosol particles may rival that of methane, with a present-day global warming effect of up to 0.3-0.4 • C .…”
Section: Introductionmentioning
confidence: 99%
“…Organic coatings can be formed on BC through condensation and/or coagulation of co-emitted primary organic aerosol (POA) and secondary organic aerosol (SOA) produced via photochemical processing. The hydrophilic nature of SOA coating has been shown to modify hygroscopicity of ambient BC for cloud droplet activation (Kuwata et al, 2009;McMeeking et al, 2011;Laborde et al, 2013;Liu et al, 2013). Increasing coating thickness may enhance light absorption of BC due to a "lensing effect" depending on the degree of particle aging (Jacobson, 2001;Cappa et al, 2012;Peng et al, 2016;Liu et al, 2017) and alter BC morphology from highly fractal to compact structures and thus their aerodynamic properties (Moffet and Prather, 2009;Schnitzler et al, 2014;Guo et al, 2016;Peng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%